Resource management under climatic risk: a case study from Niger - McCarthy, Nancy; Vanderlinden, Jean-Paul (Informa UK Limited, 2004)
In this article, we develop an empirical model of an agro-pastoral system subject to high climatic risk in order to test the impact of rainfall variability on livestock densities, land allocation patterns and herd mobility observed at the community level. Also, because grazing land is a common-pool resource, we determine the impact of cooperation on these decision variables. To capture different abilities of communities to cooperate in managing these externalities, we construct indices comprised of factors considered to affect the costliness of achieving successful cooperation. We then test hypotheses regarding the impact of rainfall variability and cooperation, using data collected in a semi-arid region of Niger. Results indicate that rainfall variability initially leads to higher densities, but the impact becomes negative as variability increases still further. This result indicates that the benefits of accumulating large herds in variable environments are eventually offset by the increasing probability of large losses. Mobility in the current period is strongly related to current rainfall, and is also positively related to long-term rainfall variability. Communities with characteristics hypothesised to favour cooperation have lower stock densities and greater herd mobility. Neither cooperation nor rainfall variability has a significant impact on the proportion of land allocated to crops or common pastures. -- Authors' Abstract